Book Notes [48, Fall 2001] - Finkel, Alvin (Labour/Le Travail, 2001)
The article briefly reviews Peter Gossage's "Families in Transition: Industry and Population in Nineteenth Century Saint-Hyacinthe;" Daniel T. Rodgers's "Atlantic Crossings: Social Politics in a Progressive Age;" Claudia Orenstein's "Festive Revolutionaries: The Politics of Popular Theater and the San Francisco Mime Troupe;" Micheal Goldfield's "The Color of Politics: Race and the Mainsprings of American Politics;" Philip Scranton's "Endless Novelty: Specialty Production and American Industrialization, 1865-1925;" "The Living Wage: Building a Fair Economy," by Robert Pollin and Stephanie Luce; Christine Cousins' "Society, Work and Welfare in Europe;" "What Workers Want," by Richard B. Freeman and Joel Rogers; and "On the Front Line: Organization of Work in the Information Economy" by Stephen J. Frenkel, Marek Korczynski, Karen A. Shire, and May Tarn.